The Impact of Corporate Ownership on Corporate Financial Performance in the Developing Markets - Makttoof, Hussein Mahdi; Jalal, Hussein Salah; Hadi, Asia Hasan; Kareem, Akeel Dakheel; Sabti, Yousif Mousa (South Asian Journal of Social Sciences and Humanities, 2025)
The ownership structure of companies is one of the main factors that affect their financial performance in developing markets. This paper purposes to study the relationship between company ownership, whether public sector, private sector and the corporate financial performance of 108 firms from bursa Malaysia from 2019 to 2024, the data from annual reports and DataStream. The research is found there are positive and significant relationship between corporate ownership and corporate financial performance. The results of studies indicate that the company's ownership structure is one of the significant factors that affect financial performance. Companies rely on different strategies to increase their profitability and improve their financial performance, and it is believed that the ownership can affect administrative decisions, the level of transparency, and governance, which is directly reflected in financial performance. These results confirm the importance of adopting effective governance strategies when designing the ownership structure in order to improve the financial performance of the firm and enhance its long-term sustainability.
Keywords: corporate ownership; corporate financial performance; developing markets